# A logarithmic integral $\int^1_0 \frac{\log\left(\frac{1+x}{1-x}\right)}{x\sqrt{1-x^2}}\,dx$

How to prove the following

$$\int^1_0 \frac{\log\left(\frac{1+x}{1-x}\right)}{x\sqrt{1-x^2}}\,dx=\frac{\pi^2}{2}$$

I thought of separating the two integrals and use the beta or hypergeometric functions but I thought these are not best ideas to approach the problem.

Any other ideas ?

After the change of variables $x=\tanh u$ (suggested by the square root) this integral reduces to $$\mathcal{I}=\int_0^{\infty}\frac{2u\,du}{\sinh u}.$$ Expanding $\displaystyle\frac{1}{\sinh u}=2\sum_{k=0}^{\infty}e^{-(2k+1)u}$ and exchanging summation and integration, we find that $$\mathcal{I}=4\sum_{k=0}^{\infty}\frac{1}{(2k+1)^2}.$$ Standard manipulations express the last sum in terms of $\zeta(2)=\frac{\pi^2}{6}$: $$\zeta(2)=\sum_{k=0}^{\infty}\frac{1}{(2k+1)^2}+\frac{\zeta(2)}{4}\quad \Longrightarrow \quad \displaystyle\mathcal{I}=3\zeta(2).$$

Let $-1\le a \le 1$ and: \begin{align*} I(a) &= \int_{0}^{1} \, \log\left(\frac{1+a\,x}{1-a\, x}\right)\frac{1}{x\sqrt{1-x^2}}\, dx \tag 1\\ \frac{\partial}{\partial a}I(a) &= \int_{0}^{1} \, \frac{1}{(1+a\, x)\sqrt{1-x^2}} + \frac{1}{(1-a\, x)\sqrt{1-x^2}} \, dx\\ &= \frac{1}{\sqrt{1-a^2}}\, \left(\arcsin\left(\frac{x+a}{1+a\, x}\right)+\arcsin\left(\frac{x-a}{1-a\, x}\right) \right) \Big|_0^1\\ &= \frac{\pi}{\sqrt{1-a^2}}\\ \therefore I(a) &= \pi\, \arcsin{a} + C \tag 2\\ \end{align*} Putting $a=0$, in $(1)$ and $(2)$, we see that $C=0$

Hence, \begin{align*} I(a) &= \int_{0}^{1} \, \log\left(\frac{1+a\,x}{1-a\, x}\right)\frac{1}{x\sqrt{1-x^2}}\, dx = \pi\, \arcsin{a} \end{align*}

and for this problem $$I(1)=\frac{\pi^2}{2}$$

• I had never seen the trick of derivating respect to an invented constant. Amazing! Jun 7, 2014 at 3:18
• Thanks, you will get used to it!
– gar
Jun 7, 2014 at 7:04
• Still, this is a very clever application of that technique, very nice, gar! Dec 2, 2014 at 2:02

The following approach uses contour integration.

First notice that

$$\int_{0}^{1} \frac{\log \left(\frac{1+x}{1-x} \right)}{x\sqrt{1-x^{2}}} \, \mathrm dx = \frac{1}{2} \int_{-1}^{1}\frac{\log \left(\frac{1+x}{1-x} \right)}{x\sqrt{1-x^{2}}} \, \mathrm dx.$$

Now let $$f(z) = \frac{\log (z+1) - \log(z-1)}{z\sqrt{(z+1)(z-1)}}$$ where $$0 \le \arg(z+1), \arg(z-1) < 2 \pi.$$

The above function is continuous across $$(1, \infty)$$ and is thus a well-defined function on $$\mathbb{C} \setminus [-1,1]$$.

On both sides of the branch cut, $$f(z)$$ has a simple pole at $$z=0$$.

And since $$f(z) \sim \mathcal{O} \left(\frac{1}{z^{3}} \right)$$ as $$|z| \to \infty$$, the residue of $$f(z)$$ at infinity is $$0$$.

So starting just above the branch cut and integrating clockwise around an indented dog-bone contour, we get

\begin{align} &\operatorname{PV} \int_{-1}^{1} \frac{\log (x+1) - \log(1-x) - \pi i}{x\sqrt{(x+1)(1-x)e^{\pi i}}} \, \mathrm dx+ \operatorname{PV}\int_{1}^{-1} \frac{\log (1+x) + 2 \pi i - \log(1-x) - \pi i }{x\sqrt{(1+x)e^{2 \pi i}(1-x)e^{\pi i}}} \, \mathrm dx \\ &= -2i \int_{-1}^{1} \frac{\log \left(\frac{1+x}{1-x} \right)}{x\sqrt{1-x^{2}}} \, \mathrm dx\\ &= \pi i \ \operatorname{Res}[f(z),0^{\text{above}}] + \pi i \ \operatorname{Res}[f(z), 0_{\text{below}}] \\ &= \pi i (- \pi) + \pi i (- \pi)\\ &= - 2 \pi^{2} i . \end{align}

(The notation $$0^{\text{above}}$$ just means that we're above the branch cut, and the notation $$0_{\text{below}}$$ just means that we're below the branch cut.)

Therefore,

$$\int_{0}^{1} \frac{\log \left(\frac{1+x}{1-x} \right)}{x\sqrt{1-x^{2}}} \, \mathrm dx = \frac{\pi^{2}}{2}.$$

• Wow, amazing. How did you 'guess' the right function to integrate? Jun 6, 2014 at 22:53
• @user111187 Really all I'm doing is integrating $f(z) = \frac{\log \left(\frac{1+z}{1-z} \right)}{z\sqrt{1-z^{2}}}$ using those branches for $(1+z)$ and $(1-z)$. I just wrote $(1+z)$ and $(1-z)$ in polar form so it's easier to understand (for me at least) what's going on. Jun 6, 2014 at 23:50
• @user111187 , i know its a long time ;) , but if u are interested i posted a complex analysis apporach where neither need to 'guess' a function nor take care of branch cuts Feb 11, 2016 at 15:24

Consider the integral \begin{align} I = \int_{0}^{1} \frac{\ln\left( \frac{1+x}{1-x} \right)}{x \sqrt{1-x^{2}}} \ dx \end{align} when the transformation $x = \tanh(t)$ is made. The resulting integral is given by \begin{align} I &= \int_{0}^{\infty} \ln\left( \frac{1+\tanh(t)}{1-\tanh(t)}\right) \frac{\cosh^{2}(t)}{\sinh(t)} \ dt \\ &= \int_{0}^{\infty} \ln\left( \frac{e^{t}}{e^{-t}}\right) \frac{\cosh^{2}(t)}{\sinh(t)} \ dt \\ &= 2 \int_{0}^{\infty} \frac{t \cosh^{2}(t)}{\sinh(t)} \ dt \\ &= 2 \left( \frac{\pi^{2}}{4} \right) \end{align} which yields \begin{align} \int_{0}^{1} \frac{\ln\left( \frac{1+x}{1-x} \right)}{x \sqrt{1-x^{2}}} \ dx = \frac{\pi^{2}}{2}. \end{align}

• How did you arrived at $\frac{\pi^2}{4}$? I know it might be something standard/obvious, but I don't know yet :) Jun 7, 2014 at 3:12
• @chubakueno I found the integral mentioned in a book I saved from Google Books. When I find the book again I will post it, but for now I seem to be at a loss of remembering which book. Jun 7, 2014 at 4:03

$\newcommand{\+}{^{\dagger}} \newcommand{\angles}[1]{\left\langle\, #1 \,\right\rangle} \newcommand{\braces}[1]{\left\lbrace\, #1 \,\right\rbrace} \newcommand{\bracks}[1]{\left\lbrack\, #1 \,\right\rbrack} \newcommand{\ceil}[1]{\,\left\lceil\, #1 \,\right\rceil\,} \newcommand{\dd}{{\rm d}} \newcommand{\down}{\downarrow} \newcommand{\ds}[1]{\displaystyle{#1}} \newcommand{\expo}[1]{\,{\rm e}^{#1}\,} \newcommand{\fermi}{\,{\rm f}} \newcommand{\floor}[1]{\,\left\lfloor #1 \right\rfloor\,} \newcommand{\half}{{1 \over 2}} \newcommand{\ic}{{\rm i}} \newcommand{\iff}{\Longleftrightarrow} \newcommand{\imp}{\Longrightarrow} \newcommand{\isdiv}{\,\left.\right\vert\,} \newcommand{\ket}[1]{\left\vert #1\right\rangle} \newcommand{\ol}[1]{\overline{#1}} \newcommand{\pars}[1]{\left(\, #1 \,\right)} \newcommand{\partiald}[3][]{\frac{\partial^{#1} #2}{\partial #3^{#1}}} \newcommand{\pp}{{\cal P}} \newcommand{\root}[2][]{\,\sqrt[#1]{\vphantom{\large A}\,#2\,}\,} \newcommand{\sech}{\,{\rm sech}} \newcommand{\sgn}{\,{\rm sgn}} \newcommand{\totald}[3][]{\frac{{\rm d}^{#1} #2}{{\rm d} #3^{#1}}} \newcommand{\ul}[1]{\underline{#1}} \newcommand{\verts}[1]{\left\vert\, #1 \,\right\vert} \newcommand{\wt}[1]{\widetilde{#1}}$ $\ds{\int_{0}^{1} {\ln\pars{1 + x \over 1 - x} \over x\root{1 - x^{2}}}\,\dd x ={\pi^{2} \over 2}:\ {\large ?}}$

With $\ds{x \equiv \cos\pars{\theta}}$: \begin{align}&\color{#c00000}{\int_{0}^{1}% \ln\pars{1 + x \over 1 - x}\,{\dd x \over x\root{1 - x^{2}}}} =\int_{\pi/2}^{0} \ln\pars{1 + \cos\pars{\theta} \over 1 - \cos\pars{\theta}}\, {-\,\dd\theta \over \cos\pars{\theta}} \\[3mm]&=-2\int_{0}^{\pi/2}{\ln\pars{\tan\pars{\theta/2}} \over \cos\pars{\theta}}\,\dd\theta \end{align}

Set $\ds{\tan\pars{\theta \over 2} \equiv t}$: \begin{align}&\color{#c00000}{\int_{0}^{1}% \ln\pars{1 + x \over 1 - x}\,{\dd x \over x\root{1 - x^{2}}}} =-4\int_{0}^{1}{\ln\pars{t} \over 1 - t^{2}}\,\dd t =-4\int_{0}^{1}{\ln\pars{t^{1/2}} \over 1 - t}\,\half\,t^{-1/2}\,\dd t \\[3mm]&=-\int_{0}^{1}{t^{-1/2}\ln\pars{t} \over 1 - t}\,\dd t =\lim_{\mu \to -1/2}\partiald{}{\mu}\int_{0}^{1}{1 - t^{\mu} \over 1 - t}\,\dd t \end{align}

With the identity ${\bf\mbox{6.3.22}}$ ( $\ds{\Psi\pars{z}}$ is the Digamma Function ${\bf\mbox{6.3.1}}$ and $\ds{\gamma}$ is the Euler-Mascheroni Constant ${\bf\mbox{6.1.3}}$ ) $$\int_{0}^{1}{1 - t^{z - 1} \over 1 - t}\,\dd t =\Psi\pars{z} + \gamma\tag{\bf 6.3.22}$$

\begin{align}&\color{#44f}{\large\int_{0}^{1}% \ln\pars{1 + x \over 1 - x}\,{\dd x \over x\root{1 - x^{2}}}} =\lim_{\mu \to -1/2}\partiald{\Psi\pars{\mu + 1}}{\mu} = \Psi'\pars{\half} =3\ \underbrace{\zeta\pars{2}}_{\ds{{\pi^{2} \over 6}}}= \color{#44f}{\Large{\pi^{2} \over 2}} \end{align}

See ${\bf\mbox{6.4.4}}$.

Denote the integral as $I$. Define $$I(a)=\int_0^1 \frac{\log\left(\frac{1+ax}{1-x}\right)}{x\sqrt{1-x^2}} dx.$$ Then $I(-1)=0$, $I(1)=I$ and \begin{eqnarray} \frac{\partial I(a)}{\partial a}&=&\int_0^1 \frac{1}{(1+ax)\sqrt{1-x^2}}dx\\ &=&\int_0^{\frac{\pi}{2}} \frac{1}{1+a\sin t}dt \quad(x=\sin t). \end{eqnarray} From this post, we have $$\frac{\partial I(a)}{\partial a}=\frac{2}{\sqrt{1-a^2}}\arctan \left(\sqrt{\frac{1-a}{1+a}}\right)$$ and hence \begin{eqnarray} I&=&\int_{-1}^1\frac{2}{\sqrt{1-a^2}}\arctan \left(\sqrt{\frac{1-a}{1+a}}\right)da\quad(a=\sin t)\\ &=&2\int_{-\frac{\pi}{2}}^{\frac{\pi}{2}}\arctan \left(\sqrt{\frac{1-\sin t}{1+\sin t }}\right)dt\\ &=&2\int_{-\frac{\pi}{2}}^{\frac{\pi}{2}}\arctan \left(\sqrt{\frac{1+\cos(\frac{\pi}{2}+t)}{1-\cos(\frac{\pi}{2}+ t)}}\right)dt\\ &=&2\int_{-\frac{\pi}{2}}^{\frac{\pi}{2}}\arctan \left(\sqrt{\frac{2\cos^2(\frac{\pi}{4}+\frac{t}{2})}{2\sin^2(\frac{\pi}{4}+\frac{t}{2})}}\right)dt\\ &=&2\int_{-\frac{\pi}{2}}^{\frac{\pi}{2}}\arctan \tan(\frac{\pi}{4}+\frac{t}{2})dt\\ &=&2\int_{-\frac{\pi}{2}}^{\frac{\pi}{2}}(\frac{\pi}{4}+\frac{t}{2})dt\\ &=&\frac{\pi^2}{2}. \end{eqnarray}

$\displaystyle J=\int^1_0 \frac{\log\left(\frac{1+x}{1-x}\right)}{x\sqrt{1-x^2}}\,dx$

Perform the change of variable $y=\sqrt{\dfrac{1-x}{1+x}}$,

$\displaystyle J=-4\int^1_0 \dfrac{\log(x)}{1-x^2}dx=-4\int_0^1 \left( \log x\times\sum_{n=0}^{+\infty}x^{2n}\right) dx=-4\sum_{n=0}^{+\infty}\left(\int_0^1 x^{2n}\log x dx\right)$

$\displaystyle J=4\sum_{n=0}^{+\infty} \dfrac{1}{(2n+1)^2}=4\left(\zeta(2)-\sum_{n=1}^{+\infty}\dfrac{1}{(2n)^2}\right)=4\times\left(1-\dfrac{1}{4}\right)\times\zeta(2)=4\times\dfrac{3}{4}\times\dfrac{\pi^2}{6}=\dfrac{\pi^2}{2}$

Note that:

0) For $s>1$, $\displaystyle \zeta(s)=\sum_{n=1}^{+\infty} \dfrac{1}{n^s}$

1) $\zeta(2)=\dfrac{\pi^2}{6}$

2) For $n\geq 0$, $\displaystyle \int_0^1 x^n\log x dx=\left[\dfrac{x^{n+1}}{n+1}\times\log x\right]_0^1-\int_0^1 \left(\dfrac{x^{n+1}}{n+1}\times\dfrac{1}{x}\right)dx=-\left[\dfrac{x^n}{n+1}\right]_0^1=-\dfrac{1}{(n+1)^2}$

After this corps has rised from the dead anyway, let me give an additional solution which is based on complex analysis but avoids the use of branch cuts, so it should be viewed as complementary to @RandomVariables approach. First, perform an subsitution $x\rightarrow\sin(t)$ which brings our integral into the form

$$I=\int_0^{\pi/2}\frac{\log(1+\sin(t))-\log(1-\sin(t))}{\sin(t)} dt$$

Now we introduce a parameter $a$ and differentiate w.r.t. it: $$I'(a)=\int_0^{\pi/2}\frac{1}{(a+\sin(t))\sin(t)}-\frac{1}{(a-\sin(t))\sin(t)} dt$$

Please note the singularity at zero is removeable, so we don't need a Cauchy principle part. We can reduce the above to

$$I'(a)=4\int_0^{\pi/2}\frac{1}{2a^2-1+\cos(2t)}dt=\int_0^{2\pi}\frac{1}{2a^2-1+\cos(t)}dt$$

we now can perform the ususal $e^{it}\rightarrow z$ substitution to map the problem onto a contour integral over the unit circle $C_+$ traveresed counterclockwise:

$$I'(a)=\frac{2}{i}\int_{C_+}\frac{1}{2z(2a^2-1)+z^2+1}dt$$

the poles are given by $z_{\pm}=1-2a^2\pm a\sqrt{a^2-1}$. At this stage a little problem appears: For $a < 1$ the poles degenerate and become double poles on our contour which we don't like, so we want to choose $a>1$ and take the limit $a\rightarrow 1_+$ in the end. For this choice of $a$ only $z_+$ lies inside our contour of integration. The corresponding residue is

$$\text{Res}(z=z_+)=\frac{1}{2 i a\sqrt{a^2-1} }$$

and therefore

$$I'(a)=\frac{\pi}{a \sqrt{a^2-1}}$$

Now what is left is integrating back to $a$. The corresponding integral is elementary and yields

$$I(a)=\pi\arctan\left(\sqrt{\frac{1}{a^2-1}}\right)+C$$

The constant of integration can be fixed by the observation that $I(\infty)=0$ yieldung $C=0$

Taking finally the limit $a\rightarrow 1_+$ yields

$$I=I(1)=\pi \times \arctan(+\infty)=\pi \times \frac{\pi}{2}=\frac{\pi^2}{2}$$

Remark: We see that we can avoid branch cuts completly but get instead new complications in choosing the correct limit of $a$ and finding the poles which are inside our contour. In summary both methods work and we just exchange some comperable hard problems at the end of the day, so it's just a matter of taste which one we choose
$$I=\int_{0}^{1} \frac{\ln\left(\frac{1-x}{1+x}\right)}{x(\sqrt{1-x^2})}dx=\int_{0}^{1} \frac{2\tanh^{-1}(x)}{x(\sqrt{1-x^2})}dx.$$ Observe $$I=\int_{0}^{1} \int_{0}^{1} \frac{2}{(1-x^2y^2)\sqrt{1-x^2}} dy dx$$ by using the fact that $$\int_{0}^{1}\frac{1}{1-x^2y^2}dy=\frac{\tanh^{-1}(x)}{x}.$$ Now to evaluate $I,$ make the change of variables $$x=\frac{\sin(u)}{\cos(v)},y=\frac{\sin(v)}{\cos(u)}$$ which has Jacobian $$\frac{\partial(x,y)}{\partial(u,v)}=1-x^2y^2.$$ The region of integration becomes the open triangle formed by the inequalities $0<u+v<\frac{\pi}{2}$ with $u,v>0.$ We now get $$I=\int_{0}^{\frac{\pi}{2}} \int_{0}^{\frac{\pi}{2}-u}\frac{2}{\sqrt{1-\left(\frac{\sin(u)}{\cos(v)}\right)^2}}dvdu=\int_{0}^{\frac{\pi}{2}} \int_{0}^{\frac{\pi}{2}-u}\frac{2\cos(v)}{\sqrt{(\cos(v))^2-(\sin(u))^2}}dvdu.$$ We can rewrite $I$ as $$I=\int_{0}^{\frac{\pi}{2}} \int_{0}^{\frac{\pi}{2}-u}\frac{2\cos(v)}{\sqrt{1-(\sin(v))^2-(\sin(u))^2}}dvdu.$$ Letting $t=\sin(v),dt=\cos(v)dv$ we get $$I=\int_{0}^{\frac{\pi}{2}} \int_{0}^{\cos(u)}\frac{2}{\sqrt{1-t^2-(\sin(u))^2}}dtdu$$ Simplifying a bit more, we get $$I=\int_{0}^{\frac{\pi}{2}} \int_{0}^{\cos(u)}\frac{2}{\sqrt{(\cos(u))^2-t^2}}dtdu.$$ Using the fact $$\int_{0}^{\cos(u)}\frac{1}{\sqrt{(\cos(u))^2-t^2}}dt=\lim_{t \rightarrow \cos(u)}\sin^{-1}\left(\frac{t}{\cos(u)}\right)=\frac{\pi}{2},$$ we see $$I= \int_{0}^{\frac{\pi}{2}} 2\left(\frac{\pi}{2}\right)du=\frac{\pi^2}{2}.$$
We have the definite integral $$I=\int_{0}^{1} \frac{\ln \left(\frac{1+x}{1-x}\right)}{x \sqrt{1-x^{2}}} \mathrm{~d} x$$ Substituting $$x=\frac{1-t}{1+t}$$, \begin{aligned} I &=-\int_{0}^{1} \frac{\ln t}{\sqrt{t}(1-t)} \mathrm{d} t \\ &=-4 \int_{0}^{1} \frac{\ln t}{1-t^{2}} \mathrm{~d} t, \text { via } t \mapsto t^{2} \\ &=-4 \sum_{k \geq 0} \int_{0}^{1} t^{2 k} \ln t \mathrm{~d} t \\ &=4 \sum_{k \geq 0} \frac{1}{(2 k+1)^{2}} \\ &=4 \lambda(2) \end{aligned} Where $$\lambda(\cdot)$$ denotes the dirichlet lambda function. Using the identity $$\lambda(s)=\left(1-2^{-s}\right) \zeta(s)$$, and the well known result $$\zeta(2)=\frac{\pi^{2}}{6}$$, which is also known as the Basel problem, we conclude that $$\int_{0}^{1} \frac{\ln \left(\frac{1+x}{1-x}\right)}{x \sqrt{1-x^{2}}} \mathrm{~d} x=\frac{\pi^{2}}{2}$$